Comparison and association of performance indicators according to set outcome and set score difference in AVP women's beach volleyball - da Costa, Yago Pessoa; Martins, Filipe Santana; Ribeiro, Lucas Roberto; García-de-Alcaraz, Antonio; Batista, Gilmário Ricarte (Frontiers in Sports and Active Living, 2025)
PurposeThis study aimed to analyze the association between technical-tactical performance indicators and the set outcome, game phase, and set score difference.MethodsIn total, 41 matches, 79 sets, and 14,959 game actions [serve: 2,879; serve reception: 2,567; set: 2,176; attack (side-out): 2,324; block: 818; dig: 1,684; set (counterattack): 1,224; and counterattack: 1,287] from two women’s Association of Volleyball Professionals Gold Series tournaments were analyzed. The independent variables were set outcome (i.e., winner or loser) and set score difference, whereas the dependent variables were points scored in each game phase, performance coefficient, and efficiency. A two-way analysis of variance was employed for comparison purposes and logistic regression was used to analyze the association between the match outcomes and the performance indicators.ResultsWinners scored more points in the K0, K2, and K3B game phases compared to losers. Similarly, higher performance coefficients and efficiencies were observed for actions performed during the defensive phase (block, dig, set, and counterattack). Moreover, the performance during the K2 and K3B phases, attack and counterattack efficiency, and the block and dig performance coefficients were associated with winning the set. The set score difference was characterized as an indicator of set balance because the differences in performance indicators between the winners and losers generally increased with greater point differentials.ConclusionIn the context of elite women's beach volleyball, although attacking was important for winning a set, the key performance indicators were mainly derived from the construction of counterattacks. In addition, the set score difference reflects the balance of the set. Therefore, these parameters can be used to guide training programs and assess team performance.